A new species of Malthonea Thomson, 1864 (Coleoptera, Cerambycidae, Lamiinae) from Ecuador - Santos-Silva, Antonio (2018)
Malthonea keili, a new species from Ecuador, is described and illustrated. A key to species of Malthonea is provided. Photographs of the types of Malthonea minima, Prymnopteryx glaucina, Malthonea ruficornis, and Ptericoptus guttatus are provided as an aid to understanding the key (photographs of the types of the last three are provided for the first time).